TRANSFORMASI PELAKSANAAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DALAM PENGEMBANGAN MASYARAKAT (COMMUNITY DEVELOPMENT) - Riyadi, Riyadi (Fakultas Ilmu Politik dan Ilmu Sosial, Universitas Brawijaya, 2010)
This article discuss about existence of corporate is not coincidence, but it is something âgivenâ, therefore corporate cannot detached in the environment. Company prosperity not ethical if it enjoyed by self, while the citizen has a problem in economic and life. CSR (Corporate Social Responsibility) program is not just euphoria for corporate responsibility to citizen, but is needed a big change from âhaving funâ becomes âmandatory activitiesâ and finally become a requirement of corporation.A harmony life and responsibility each other between corporate and stakeholder and the environment is a big result from the existence of corporate, because a corporate with a good CSR is sustainable in the end.A good CD (Community Development) need some conditions, like, good framework, government role, involvement of stakeholders, performance assessment and the change and the change of execution pattern from CD to citizen become self-supporting and CSR role be development to importance which enough wide. Â Key words: Corporate Social Responsibility, Community Development